PEMANFAATAN E-GOVERNMENT DALAM PELAKSANAAN KINERJA PEGAWAI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL STUDI KASUS DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN PANGKEP SULAWESI SELATAN - PALI, SOVIA TIRZA TANDI; TAMPI, GUSTAAF; LONDA, VERY (Sam Ratulangi University, 2021)
With the existence of E-government as an information and communication technology within thegovernment, efforts are being made to further improve the organization and management of government.This is intended to be able to carry out and carry out their duties and functions effectively and efficiently.This study uses a qualitative approach. Data obtained from interviews, observations and documents. Dataanalysis was carried out through data reduction, data presentation, and conclusion drawing. The findingsof this study are that the use of e-government realized by employees of the Department of Population andCivil Registration can benefit the performance of employees in providing existing services to thecommunity, based on the provision of good and effective services, in increasing efficiency, and inproviding information to the public. evenly. The government should further increase the existingresources to support performance. Because this is one of the factors that influence the extent to which theuse of e-government can be put to good use. Be more active in monitoring community activities onexisting platforms or social media, so that the community gets a quick response from employees, alsoremains active in socializing existing programs and providing quality information.Keywords: utilization, e-government, employee performance.